2015
DOI: 10.1016/j.jenvman.2015.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of riparian vegetation: A global review of implementation and evaluation approaches in the international, peer-reviewed literature

Abstract: We examined how restoration of riparian vegetation has been implemented and evaluated in the scientific literature during the past 25 years. A total of 169 papers were read systematically to extract information about the following: 1) restoration strategies applied, 2) scale of monitoring and use of reference sites, 3) metrics used for evaluation, and 4) drivers of success. Hydro-geomorphic approaches (e.g., dam operations, controlled floods, landform reconfiguration) were the most frequent, followed by active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(105 citation statements)
references
References 51 publications
1
100
1
3
Order By: Relevance
“…The question remains, however, whether this level of connection is unique to Tamarix removal projects, or if there has been an overall improvement in communication since the last large‐scale assessment of the knowledge gap. This study presents contrasting results to the nationwide study of riparian restoration practitioners that found a lack of information transfer and adherence to scientific recommendations (Bernhardt et al ), as well as of a global literature review of riparian restoration practices over the last 25 years that showed poor use of controls and low degree of comprehensive monitoring (González et al ). Given that the recent publications calling for a narrowing of this knowledge/communication gap do not quantitatively assess the purported gap, similar studies conducted in other systems would aid in the effort to identify where there is still a large gap and also how boundary organizations contribute to restoration success.…”
Section: Discussioncontrasting
confidence: 64%
“…The question remains, however, whether this level of connection is unique to Tamarix removal projects, or if there has been an overall improvement in communication since the last large‐scale assessment of the knowledge gap. This study presents contrasting results to the nationwide study of riparian restoration practitioners that found a lack of information transfer and adherence to scientific recommendations (Bernhardt et al ), as well as of a global literature review of riparian restoration practices over the last 25 years that showed poor use of controls and low degree of comprehensive monitoring (González et al ). Given that the recent publications calling for a narrowing of this knowledge/communication gap do not quantitatively assess the purported gap, similar studies conducted in other systems would aid in the effort to identify where there is still a large gap and also how boundary organizations contribute to restoration success.…”
Section: Discussioncontrasting
confidence: 64%
“…The few evaluations of this restoration method published to date have shown increases in riparian habitat heterogeneity and establishment of pioneer riparian plants when compared with unrestored control sites (e.g., Florsheim and Mount, 2002;Gonzalez et al, 2017a;Gothe et al, 2016;Hering et al, 2015;Jahnig et al, 2009;Poppe et al, 2016;Rohde et al, 2005; note that in some of these papers the restoration actions are semantically confounded with the restoration goal as this restoration technique is generally referred as to "channel widening"). Surprisingly though, and despite recommendations (Bernhardt et al, 2007;Gonzalez et al, 2015), we are unaware of any study taking into account river conditions prior to restoration (before-after-reference design). Most of the abovementioned published evaluations of longitudinal structures manipulation have studied their implementation over short river sections, usually less than 2 km and even less than 300 m. Such a local-scale approach to river restoration might not be sufficient to maintain the key abiotic and biotic processes that sustain life in riparian areas, such as erosion, sedimentation, propagule dispersal, plant establishment, and organic matter decomposition, which are driven by factors, such as the flow regime or the flooding extent, that operate at multiple, higher and nested spatial levels, including segments of several kilometers in length, landscape units, and entire catchments (Gurnell et al, 2016).…”
Section: Res-6mentioning
confidence: 98%
“…In this social context, this type of restoration actions has been employed much less often than needed, and its effectiveness in restoring riparian vegetation has not been frequently assessed (Gonzalez et al, 2015). The few evaluations of this restoration method published to date have shown increases in riparian habitat heterogeneity and establishment of pioneer riparian plants when compared with unrestored control sites (e.g., Florsheim and Mount, 2002;Gonzalez et al, 2017a;Gothe et al, 2016;Hering et al, 2015;Jahnig et al, 2009;Poppe et al, 2016;Rohde et al, 2005; note that in some of these papers the restoration actions are semantically confounded with the restoration goal as this restoration technique is generally referred as to "channel widening").…”
Section: Res-6mentioning
confidence: 99%
“…Operational tools to quantify human influence (through hydraulic management, stocking, recreational use) and environmental drivers (temperature, water quality) on fish populations in reservoirs still remain scarce. In environments where the littoral zone is altered, hydromorphological rehabilitation programs are often implemented (Gonzalez et al, 2015). Any study that could provide insight into the impact of a hydromorphological restoration on the fish population is valuable (e.g.…”
Section: Seasonal Pattern Of Habitat Use and Preferencementioning
confidence: 99%